Estrategias del poder sagrado: la construcción de la jerarquía y la autoridad en el budismo zen Argentino = Sacred power strategies : the construction of hierarchy and authority in Argentine Zen Buddhism - Carini, Catón Eduardo (Ciencias sociales y religión, 2006)
This article investigates the processes through which the dimensions ofpower, hierarchy and authority are constructed within a zen buddhist group locatedin Argentina. With this goal, we analize the figure of the “lineage of the patriarchs”of wich the zen master, being the last one of them, receives his authority, and therites that legitimate his position. Also, we present a series of conceptions thatdepict the master as a realized Buddha, in possesion of a great amount of vitalenergy or ki, that provides him with magical powers. This strenght is related to hiscapacity as ruler of the buddhist community, and to a revolutionary political attitudetowards the outside of the community. This takes us to the problem of the inclusionof zen buddhism in the framework of the New Age, as it presents aspects, such asa solid structure of authority, opposite to the ones commonly accepted featuresof this movement.